2023
DOI: 10.3390/educsci13010094
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the User Interface Design Frameworks of Current Mobile Learning Applications: A Systematic Review

Abstract: Online learning has replaced traditional face-to-face classroom instruction in the educational system. Learning via mobile, or mobile learning, is one of the solutions that most learners use since it is less expensive and easier to adopt on the go. However, in addition to hindering information transfer, issues such as small screen size and bad interface design can also make learning more cognitively demanding. This paper presents a systematic literature review on the user interface design of mobile learning ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Studies have shown that welldesigned interfaces increase user satisfaction, engagement, and learning outcomes. For example, a study by Faudzi et al (2023) investigated the impact of interface design on user engagement in a mobile learning application for STEM education. The study found that participants rated the application more positively with intuitive navigation, clear layout, and visually appealing design elements.…”
Section: User Experience and Interface Designmentioning
confidence: 99%
“…Studies have shown that welldesigned interfaces increase user satisfaction, engagement, and learning outcomes. For example, a study by Faudzi et al (2023) investigated the impact of interface design on user engagement in a mobile learning application for STEM education. The study found that participants rated the application more positively with intuitive navigation, clear layout, and visually appealing design elements.…”
Section: User Experience and Interface Designmentioning
confidence: 99%